(3TQM GdQSGdI GdbjGSjI ddHgdhGfjs - (3OOg CafOj, eMeO OOg Hf eUWai Hf MHjH, J (B1146 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; fMeOc jG ef aVdfG HGdefWb GdaUjM hHYO ajbhd eMeO Hf eUWai GdCQV Qhej deG cGJ GdQSGdI GdbjGSjI eTJedI Ydi ahGFO cKjQI hdWGFa GdCbjSI SCdfj HYV GdWdHI Cf CbjO dge eG ajgG ef GdObjbI hdjS dgG TQM jRjd ZhGeVgG GdecfhfI cJHJ dgG TQMGs
(3BNQgG (B:s
(3ccbhdc cd eDef TQja HGdfSHI Edi GdcGaQ hdG TjA ef GdMGaQ HcGaQ (B( (3cPG (B) (3aEfg dG jfJL cdjI hdG LRFjI hZjQ Pdc dG jNai Ydi GdeJJHY GdeJCed HGdJCed GdKGbH hEf Naj Ydi GdeMLhH GdHdjO hdPG de jYJHQ hGdTQhW hEf hbY aj cdGege CMjGfG (B( (3cPG (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 100s
(3eYLe GdeDdajf (B3 / 717s
(3X(B3s
(3gOjI GdYGQajf (B2 / 321s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs